Potret Teknik Lahan Sawah Di Provinsi Bali: Produksi, Produktivitas Dan Efisiensi - Tamba, I Made (Jurnal Ekonomi Pertanian dan Agribisnis, 2024)
Among consumers, rice has grown to be a very popular item, surpassing the popularity of other goods categorized as food. Given the strategic importance of rice in Indonesian society, the government has worked to create an environment that will support the continued production of rice through a number of programs. The issue of growing agricultural land conversion to non-agricultural uses, however, poses a serious danger to the continuation of the country's rice production. The problem of declining rice crop productivity doesn't end there; it still poses a threat to the goal of rice self-sufficiency. This research aims to analyze (1) the growth rate of rice harvest area, (2) the growth rate of rice productivity, and (3) the efficiency of paddy field techniques. The time series data used in this study are from BPS-Statistics Indonesia and span the years 2017 to 2021. Data regarding lowland rice yield, production, and harvest are among the information gathered. The technical efficiency of paddy fields was examined using Data Envelopment Analysis (DEA) method. According to the research findings, there is still room for improvement in the technical efficiency of paddy fields, despite negative growth rates for both the rice harvest area and rice output.